2015
DOI: 10.1038/ncomms9465
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically activated switching of Si-based single-molecule junction as imaged with three-dimensional dynamic probe

Abstract: Understanding and extracting the full functions of single-molecule characteristics are key factors in the development of future device technologies, as well as in basic research on molecular electronics. Here we report a new methodology for realizing a three-dimensional (3D) dynamic probe of single-molecule conductance, which enables the elaborate 3D analysis of the conformational effect on molecular electronics, by the formation of a Si/single molecule/Si structure using scanning tunnelling microscopy (STM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“… 1 4 Efforts in molecular electronics have demonstrated the use of silicon surfaces as electrodes 5 9 and amino-silanes as chemical binding groups to the electrodes. 10 , 11 Moreover, investigation on cyclohexasilane 12 has shown that conformations affect the molecule's electronic structure and another study on [2,2,2]bicyclic carbosilane systems 13 has suggested that different disilanylene bridges in the cage compounds do not act as parallel resistors. Recently we synthesized linear chains of molecular silicon that demonstrated conductance decay properties comparable to those of π-conjugated hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“… 1 4 Efforts in molecular electronics have demonstrated the use of silicon surfaces as electrodes 5 9 and amino-silanes as chemical binding groups to the electrodes. 10 , 11 Moreover, investigation on cyclohexasilane 12 has shown that conformations affect the molecule's electronic structure and another study on [2,2,2]bicyclic carbosilane systems 13 has suggested that different disilanylene bridges in the cage compounds do not act as parallel resistors. Recently we synthesized linear chains of molecular silicon that demonstrated conductance decay properties comparable to those of π-conjugated hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Furthermore, recent progress in nanometer-scale fabrication techniques combined with optical technologies has allowed optical experiments on current-carrying molecular junctions. [5][6][7][8][9][10][11][12][13][14][15][16][17] These advances bring molecular electronics and optical spectroscopy together, leading to the emergence of molecular optoelectronics. 18,19 In the optical response of current-carrying molecular junctions, the electrons participate in both conductance and optical scattering.…”
mentioning
confidence: 99%
“…Additional spectroscopic tools that have also been employed in non-equilibrium conditions include surface-and tip-enhanced Raman spectroscopy which now allows for measurements on the Angström scale [12][13][14][15][16] , studies of electronic pathways in redox proteins 17 , utilizing 3D dynamic probe of single-molecule conductance to explore conformational changes 18 , and energy-resolved atomic probes 19 , to name just a few.…”
Section: Introductionmentioning
confidence: 99%